The impact of Artificial Intelligence on the job market in Uganda, a third world country - Rhona Wacha Adong (Uganda Christian University, 2025)
This research seeks to assess the impact of Artificial Intelligence on the job market in Uganda. Through this research the impact of Artificial Intelligence falls both on the positive and negative impact. Three effects were discovered to include; the displacement effect where there will be massive loss of jobs but Uganda being a third world country presents signs that this could take a while to happen, the reinstatement effect which covers creation of new jobs which could take years. The productivity effect that would see enhancement in the different jobs in place. However, these effects will take long before realization in the different aspects in Uganda because development is slow.
Undergraduate